2003
DOI: 10.1038/sj.leu.2403242
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lymphocytic leukemia with 6q− shows distinct hematological features and intermediate prognosis

Abstract: Cytogenetic and fluorescence in situ hybridization studies were successfully performed in 217 chronic lymphocytic leukemia (CLL). In all, 13 patients with 6q21 deletion were identified and characterized in comparison with 92 patients with 'favourable' karyotype (normal or 13qÀ), 69 cases with 'intermediate risk'(1-2 anomalies) and 43 cases with 'unfavourable' karyotype (complex, 11qÀ or 17pÀ). Six out of 13 cases with 6qÀ showed an excess of atypical lymphocytes, a finding confirmed at the histologic level; 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
3
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 35 publications
(42 reference statements)
5
73
3
4
Order By: Relevance
“…2. In the present study, deletion of 6q was detected in 5% of papients as as compared to 3-6% reported before [14,15].…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…2. In the present study, deletion of 6q was detected in 5% of papients as as compared to 3-6% reported before [14,15].…”
Section: Discussionsupporting
confidence: 45%
“…Deletion of 6q is a rare abnormality detected in 3-6% of patients and represents a distinct cytogenetic and clinicobiological entity with intermediate prognosis [14,15].…”
mentioning
confidence: 99%
“…3,8 Caraway et al 30 found abnormal FISH signal patterns in 81% of CLL/SLL cases on fine-needle aspirates, and Flanagan et al 29 described at least one cytogenetic aberration in all 18 patients analyzed on lymph node biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…The 17p/p53 deletion and the 11q-deletion involving the ATM gene were associated with an unfavorable outcome. 4,5 Evidence was also provided that 6q deletion may be found in a subset of SLL 6 and CLL with hyperleukocytosis and intermediate outcome 7,8 and that 14q32 translocations involving the immunoglobulin heavy (IgH) chain gene may be associated with unfavorable prognosis. 9,10 A characteristic histopathologic feature of SLL/CLL is represented by 'proliferation centers' (PCs), which consist of regularly distributed pale areas without a mantle with numerous prolymphocytes and paraimmunoblasts, resulting in a pseudofollicular pattern.…”
Section: Introductionmentioning
confidence: 99%
“…The following markers were tested in all patients by multicolor flow cytometry analysis, as described previously, 24 using a 30% cutoff level for positivity in the lymphocyte gate: cluster of differentiation 5 (CD5)-phycoerythrin (PE), CD5 allophycocyanin (APC), CD19-fluorescein isothiocyanate (FITC), CD19-peridinin chlorophyll protein (PerCP)-cyanine 5.5 (Cy5.5), CD19-PE-Cy7, CD22-PE, CD23-PE, CD38-PE, anti-j-FITC, anti-k-PE (Becton Dickinson, Milan, Italy), CD10-FITC, FMC7-FITC, immunoglobulin G (IgG)-FITC, IgM-FITC, IgA-FITC, IgD-FITC (Dako, Milan, Italy), and fchain-associated protein kinase 70 (ZAP70)-AlexaFluor-488 (Valter Occhiena, Torino, Italy).…”
Section: Flow Cytometry and Circulating Endothelial Cell Quantificationmentioning
confidence: 99%